Ensino e aprendizagem de astronomia sob a perspectiva do ensino por investigação e da teoria dos campos conceituais a partir da base nacional comum curricular - Reis, Michele Tamara (2023)
Aiming for contributions to the area of Science Teaching, this thesis presents research based on the Theory of Conceptual Fields and Teaching by Investigation to support the teaching and learning process of Astronomy. Thereby, relations were initially established between the interests of students in the Final Years of Elementary School on Astronomy and what is presented in textbooks and educational documents. The result indicated closeness between the students interests and the concepts related to Astronomy suggested in the National Common Curricular Base (BNCC) and distance from the contents present in textbooks. After this finding, a systematic review was carried out on theses and dissertations defended between 2009 and 2019, for the purpose of order to investigate what Astronomy was taught to students in the Final Years of Elementary School, as well as to verify the presence of a basis in the Theory of Conceptual Fields and Research Teaching. The systematic review resulted in two dissertations based on the didactic approach of Teaching by Investigation, and neither on the Theory of Conceptual Fields. Given this result, and the blanks found in the literature about the lack of research based on these references, a bibliographical review was carried out on the foundations of the Theory of Conceptual Fields and Teaching by Investigation, pointing the importance for Science Teaching. From then on, four Investigative Teaching Sequences (SEI) were elaborated based on the Theory of Conceptual Fields and on Teaching by Investigation. Each SEI was prepared according to the Astronomy concepts present in the Thematic Unit Earth and Universe of the BNCC, specific for the 6th, 7th, 8th and 9th grade of Elementary School. Ergo, the application of the SEI occurred in three different schools, being entitled “Astronomy Project”. The objective was to investigate the indication of learning about the Conceptual Field of Astronomy presented by students of the Final Years of Elementary School when participating in Investigative Teaching Sequences elaborated from the Thematic Unit Earth and Universe of the Base Nacional Comum Curricular. To this end, at the end of the SEI, an Astronomy Quiz was held, consisting of closed questions on the main concepts addressed throughout the didactic interventions. The research results indicated satisfactory performance of the students, as well as significant signals of learning in relation to the main concepts related to the Conceptual Field of Astronomy, addressed throughout the SEI. However, 6th grade students had greater trouble understanding some concepts, while 7th, 8th and 9th grade students did not have significant trouble regarding the concepts covered. Therefore, this thesis recognizes and highlights the potential of the references used for the teaching and learning process of Astronomy.